High Temperature Chloride Corrosion Behavior of 904L:AlFeNiMoNb High-Entropy Alloy - Bai, Lingyun; Peng, Wenyi; Men, Dandan; Zhu, Jun; Wu, Xuecheng; Shi, Xiongtao; Xiang, Junhuan; Deng, Xiaohua; Wang, Yuqing; Sun, Zuxiang; Yu, Siqi; Wei, Xiang (Frontiers in Materials, 2021)
In order to obtain high cost-effective coating materials working in chlorine containing environment at high temperature, 904L super austenitic alloy modified by AlFeNiMoNb alloy (904L:AlFeNiMoNb) was obtained by vacuum arc melting process. 904L:AlFeNiMoNb high-entropy alloy has a similar phase component with the AlFeNiMoNb alloy, but a more homogenous microstructure than that of the AlFeNiMoNb alloy. High temperature chloride corrosion tests for 904L, AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy were carried out under N2-2.6 vol.%CO2-1.3 vol.%O2-2700 vppm HCl gaseous environment at 700 °C and 800 °C for 55 h, respectively. Due to the volatilization of FeCl2, weight change curves of 904L alloy at 700 °C and 800 °C showed obvious weight loss. Especially at 800 °C, the weight loss of the corroded 904L sample was 10 times that of corroded sample at 700 °C. Different from the weight loss situation of 904L sample, both of AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy showed small weight gains under the corrosion temperature of 700 °C, while the latter gained half as much weight as the former. When the corrosion temperature was raised to 800 °C, AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy showed flat weight change curves with little weight loss. Weight loss for the AlFeNiMoNb and 904L:AlFeNiMoNb high-entropy alloy were 1.35138 mg/cm2 and 0.0118 mg/cm2, respectively. The high temperature chloride corrosion resistance of 904L:AlFeNiMoNb high-entropy alloy is higher than that of 904L and AlFeNiMoNb at both 700 °C and 800 °C. Meanwhile, on the basis of the morphology and composition results of the corroded samples, combined with the thermodynamic calculation, the high temperature chloride corrosion mechanics of the tested alloys were discussed.